Characteristics of Sepsis or Acute Pyelonephritis Combined with Ureteral Stone in the United States: A Retrospective Analysis of Large National Cohort - Francesco Del Giudice; Koo Han Yoo; Sinyeong Lee; Jin Kyu Oh; Hyuk Jin Cho; Sang Youn Kim; Gyeong Eun Min; Sang Hyub Lee; Wansuk Kim; Shufeng Li; Wuran Wei; Jianlin Huang; et al. (Applied Sciences, 2022)
To identify the characteristics of patients with sepsis or acute pyelonephritis (APN) combined with ureteral calculi and to analyze the risk factors in its causation. Methods: We included patients with sepsis or APN caused by ureteral calculi who received treatment in the United States from January 2003 to December 2017 using the Optum® deidentified Clinformatics® Datamart. Demographic factors and risk factors for the receipt of sepsis or APN were subsequently analyzed for statistical significance. Results: Of 467,502 urinary stone patients, age-matched multivariate analysis revealed that a history of urinary tract infection (OR 11.31, 95% CI 10.68–11.99, p < 0.0001) and female gender (OR 2.73, 95% CI 2.62–2.84, p < 0.0001) were significantly related to an increased risk of sepsis or APN. Conversely, a previous past medical history of urolithiasis (OR 0.91, 95% CI 0.87–0.95, p < 0.0001) and cancer (OR 0.91, 95% CI 0.87–0.95, p < 0.0001) were associated with a decreased risk of sepsis or APN. With regards to comorbidities, when more than one comorbidity was present, there was an additive effect with higher OR point estimates, rising to 11.31 (10.68–11.99) when three or more comorbidities present. History of urinary tract infection and female gender are risk factors for sepsis or APN in patients with ureteral calculi. Conclusions: This large national cohort reveals the characteristics of sepsis or APN combined with ureteral stone and provides an important baseline for the treatment of urolithiasis in the future.